War veterans, international politics, and the early Cold War, 1945–50. Issue 4 (2nd October 2018) - Alcalde, Ángel
Abstract: Despite the importance of war veterans issues in many nation-states after World War II, Cold War historians have never examined international veteran politics. By analysing scholarship and hitherto unexamined primary sources, this article surveys the realignments taking place in veteran politics in different countries and investigates the process leading to the creation of the World Veterans Federation in 1950. It argues that the Cold War profoundly shaped international veteran politics after 1945, and that veterans' international organisations became political instruments and spaces of Cold War tensions. By revealing how Cold War events, particularly the Korean War, created opportunities for the veterans' international activities under American leadership, this article offers insights into the impact of the Cold War on the transnational sphere.